Attention control in a trial of an online psychoeducational intervention for caregivers. Issue 3 (25th January 2022) - Kovaleva, Mariya; Nocera, Joe R.; Hepburn, Kenneth; Higgins, Melinda; Nash, Rachel; Epps, Fayron; Brewster, Glenna; Bilsborough, Elizabeth; Blumling, Amy A.; Griffiths, Patricia C.
Abstract: In reports of randomized controlled trials, thorough description of the attention control condition has been recommended, yet is frequently lacking. The Tele‐Savvy Caregiver program for informal caregivers of persons living with dementia was tested in a randomized controlled trial with an attention control condition. The purpose of this trial was to test Tele‐Savvy's efficacy in reducing the negative effects of caregiving on caregivers, promoting quality of life for persons living with dementia, and improving caregiver mastery. We describe the design and implementation of and examine the outcomes associated with the attention control condition. Caregivers were randomized to the immediate Tele‐Savvy (active condition), Healthy Living (attention control), or waitlist. The attention control content was focused on healthy lifestyle and was not intended to affect the outcomes that Tele‐Savvy targeted. The attention control group was similar to Tele‐Savvy in the intervention structure and duration: it consisted of seven weekly group videoconferences and 36 video lessons. Data on outcomes of caregivers and persons living with dementia were collected at baseline and 3 and 6 months postbaseline. Multilevel mixed effects models were used to determine changes in the outcomes. One hundred and eleven caregivers were randomized to the attention control condition (attrition 21.6%). Eighteen formative assessment interviews focusing on caregivers' experience in the attention control condition were conducted. The attention control condition completers had no statistically significant changes in the variables that Tele‐Savvy targeted. These results may be used in the design and implementation of attention control conditions in behavioral intervention research.